2007
DOI: 10.1007/s00192-007-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum anal sphincter lacerations in a population with minimal exposure to episiotomy and operative vaginal delivery

Abstract: This case-control study was designed to identify risk factors for anal sphincter lacerations (ASL) in a multicultural population where episiotomies and operative vaginal deliveries are rarely performed. Cases were subjects with ASL delivered between July 1997 and June 2003. Two controls were selected for each case matched for gestational age. Independent variables collected included age, race/ethnicity, parity, tobacco use, medical conditions, episiotomy, operative vaginal delivery, epidural use, and infant we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our findings support that the second stage of labor does not significantly negatively impact global postpartum pelvic floor function at 6 months postpartum in a low-episiotomy, low-operative delivery setting. While our vaginal birth group was cared for by midwives, the low rates of episiotomy and operative delivery are reflective of the low rates of these interventions of all practitioners who attend birth in our labor and delivery unit 20,21 . In addition, our practices are reflective of US national trends in the performance of episiotomy and operative delivery and are reflective of evidence based care 22, 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support that the second stage of labor does not significantly negatively impact global postpartum pelvic floor function at 6 months postpartum in a low-episiotomy, low-operative delivery setting. While our vaginal birth group was cared for by midwives, the low rates of episiotomy and operative delivery are reflective of the low rates of these interventions of all practitioners who attend birth in our labor and delivery unit 20,21 . In addition, our practices are reflective of US national trends in the performance of episiotomy and operative delivery and are reflective of evidence based care 22, 23 .…”
Section: Discussionmentioning
confidence: 99%
“…We found several studies that reported an association between smoking and OASIS with inconsistent results. One large population study suggested a 40% (unadjusted OR 0.6, 95% CI 0.6–07) lower risk of OASIS among women who smoked at the end of the pregnancy (n = 28,566 of 266,037) [22] whereas the other studies that examined considerably lower numbers of cases found no significant associations [23][26]. This study was undertaken to evaluate whether smoking during pregnancy was associated with OASIS, one of the markers of childbirth injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Mean offspring birthweight is higher in parous than in primiparous mothers and for that reason, shoulder dystocia may occur more often in parous mothers (15,16). However, complications at delivery associated with birthweight, such as prolonged labor and rupture of the anal sphincter, are more common at first delivery (17–19). The role of parity related to shoulder dystocia remains unclear, and results of previous studies have been contradictory (13,19,20).…”
Section: Introductionmentioning
confidence: 99%